Dimensions of Organisational Culture in Quantity Surveying Firms in Nigeria (Construction Economics and Building, 2014)
The functionalist paradigm of organisational culture (OC) views culture as a variable subject to conscious manipulation and control in order to solve organisational challenges. Therefore, this paper provides information on how OC is a solution to the challenges in Quantity Surveying firms (QSFs).  This was achieved by eliciting the dimensions of OC in forty two QSFs in Lagos, Nigeria, which are the business, people and external environment dimensions. The paper concludes that OC is a relevant solution to the identity and management related challenges in QSFs. Specifically, the paper informs on the implications of business and people dimensions of OC as a solution to the identity challenges, as well as on the implication of the external environment dimension of OC to the management challenges. Based on the findings, practical implications and recommendations were directed at the management and employees QSs in QSFs and Quantity Surveying researchers.